STUDENTS' DIFFICULTIES IN WRITING EXPOSITORY ESSAY: A PHENOMENOLOGICAL STUDY - Ivanna Maria Long; Susana Teopilus (Widya Mandala Surabaya Catholic University, 2023)
Writing, one of the language skills, is considered difficult for some students, especially EFL students. The present research, a phenomenological study, aims to find out the students’ difficulties, the factors affecting their difficulties, and the strategies for overcoming their difficulties in writing expository essays. The participants were three students, taken by using purposive sampling, in a private university in Surabaya. The instruments used in this research were observational fieldnotes, rubrics, Focus Group Discussion guidelines, and Interview protocols. The research findings show that the research participants had difficulties in the five components of writing, namely content, vocabulary, language use, mechanics, and organization. The common difficulties the participants faced were related to word choice, finding and developing ideas, verb tense, run-on sentences, spelling, punctuation, and writing the thesis statements and topic sentences. There were internal and external factors that affected their difficulties, but most of the factors were internal. The most common factors were that the participants did the assignments at the last minute or in a hurry, felt sleepy and lazy, and were afraid of plagiarism. Some ways of overcoming their difficulties were finding more ideas and materials on the Internet, discussing the topic and content with their friends and lecturers, writing the ideas in Indonesian before translating them into English, using common vocabulary, learning new vocabulary, finding the opposites and synonyms of some words, doing paraphrase, using Grammar-checking tools, learning from the previous mistakes, paying more attention to the essay structure, making an outline, learning more basic English grammar, revising the mistakes based on the lecturer’s feedback, and listening to music when writing the essays.